Pengaruh Berbagai Dosis Jus Buah Sirsak (Annona muricata L.) Terhadap Penurunan Kadar Kolesterol Low Density Lipoprotein (LDL) Serum Tikus Putih (Rattus norvegicus) Dislipidemia - Tia, Hesti Dwi; Sistiyono, Sistiyono; Hendarta, Narendra Yoga (POLTEKKES KEMENKES YOGYAKARTA, 2014)
Consumption of excessive fat in the food that we consume daily can increase cholesterol, LDL cholesterol and triglycerides in the blood that is called dyslipidemia. Diet, exercise and drugs are the effort can be done to lower the lipid levels. The herbs have been widely used as an alternative to lower cholesterol levels because the active substances contained antihiperlipid properties. Soursop has many benefits in curing some diseases. Soursop contains an active ingredient that can lower LDL’s cholesterol levels, including vitamin C, fiber and niacin. Therefore, the researchers wanted to do experiment using soursop as an alternative for lowering LDL’s cholesterol levels in dyslipidemia white rat serum.The purpose of this experiment was to determine the effect of various doses of soursop juice to decrease of LDL’s cholesterol levels in dyslipidemia white rat serum.This experiment used pre-test and post-test with control group design. Soursop juice doses used was at 0,9; 1,8 and 2,7 g / 200 g BW of white rat. The data were processed using descriptive and statistics by the Kolmogorov Smirnov Test, One Way ANOVA, Post Hoct Test and linear regression in SPSS 16.0 for Windows.The results of this experiment was the percentage decrease of LDL cholesterol levels in the white rat serum of various doses soursop juice, which is 0,9 g / 200 g BW of 46,19%, a dose of 1,8 g / 200 g BW of 52,30 % and a dose of 2,7 g / 200 g BW of 61,62%.There was the effect of various doses of soursop juice to decrease LDL’s cholesterol levels in dyslipidemia white rat serum. The greater the dose of soursop juice given, the greater the reduction in LDL’s cholesterol levels in the serum of dyslipidemia white rat.